The Essential Dimensions of Health According to the Maqasid al-Shariʿah Frameworks of Abu Ishaq al-Shatibi and Jamal-al-Din-ʿAtiyah - Padela, Aasim I. (IIUM Medical Journal Malaysia, 2018)
Contemporary Muslim thinkers have shown increasing interest in the higher objectives of Islamic law, maqaṣid al-shariah for reasons of utility and flexibility. Inductively derived from scriptural source-texts and the inherited legal canon, the maqasd have proven to be useful in interfaith dialogue and in addressing modern contexts because they are rationally accessible and can incorporate knowledge coming from the natural and social sciences as well as the humanities. In this paper, I examine the maqasid for applicability to the healthcare context. Specifically, I will describe the maqaṣid formulae of Islamic scholars Abu Ishaq al-Shatibi and Jamal-al-Din-ʿAṭiyah (Gamal Eldin Attia) and use them to generate theoretical models of the essential dimensions of human health. During my analyses of these authors’ frameworks, I will examine their views on how the maqaṣid are discovered, and on focus on their discussions regarding the preservation of human life and intellect. I will also compare the relative relevance of their models to modern biomedicine in terms of their “openness” to data coming from the health sciences and in light of contemporary knowledge about the determinants of health.